(untitled) - Anderson, Joseph I. (New Jersey, 1982)
The Japanese have probably produced the most original, complex, and entertaining films in the international cinema. Anderson and Ritchie tell the story of the Japanese film from a number of different perspectives. Beginning with a compelling chronological overview, they go on to describe Japanese film through its various techniques, its directors, its actors and its audiences. Few industries have had a more fascinating history and Anderson and Ritchie do it justice in this fine and informative book.
Keywords: Motion pictures; History; Japan